Studi Analisis Saintifik Homeschooling Jadi Pilihan Parents Pasca Pandemi - Azizah, Aviaska; Sari, Indah Purnama; Prasetyono, Hendro (Journal of Academia Perspectives, 2024)
Innovative learning needs to be implemented, there are many learning obstacles that occur in children. Cases of bullying, excessive anxiety, difficulty concentrating. This research uses the method of reviewing school data and archives, in the form of forms given to parents for school promotion in the form of a questionnaire. A total of 71 students stated that they were waiting to continue their studies at home schooling, 36 parents stated that they would still send their children to school. Learning barriers have a percentage of 31.25% while instantaneous time and distance is 31.25%, children's health is at 25% and children's lack of socializing is 3.12%.This phenomenon makes parents careful in responding to their children's needs. Various programs have been considered. Kak Seto Depok's homeschooling comes with exciting and fun learning. Kak Seto Depok's homeschooling also has a variety of programs, because it sees the variety of cases that occur in the world of education.